Mathematical analysi a concise introduction - Yong, J. (Jiongmin), 1958- (Singapore : World Scientific, 2021)
"Mathematical analysis serves as a common foundation for many research areas of pure and applied mathematics. It is also an important and powerful tool used in many other fields of science, including physics, chemistry, biology, engineering, finance, and economics. In this book, some basic theories of analysis are presented, including metric spaces and their properties, limit of sequences, continuous function, differentiation, Riemann integral, uniform convergence, and series. After going through a sequence of courses on basic calculus and linear algebra, it is desirable for one to spend a reasonable length of time (ideally, say, one semester) to build an advanced base of analysis sufficient for getting into various research fields other than analysis itself, and/or stepping into more advanced levels of analysis courses (such as real analysis, complex analysis, differential equations, functional analysis, stochastic analysis, amongst others). This book is written to meet such a demand. Readers will find the treatment of the material is as concise as possible, but still maintaining all the necessary details"--Publisher's website.
Preface -- Metric spaces and limits for sequences -- Functions on metric spaces -- Differentiation -- Riemann integrals -- Uniform convergence -- Series -- Appendix : the real number system -- Bibliography -- Index.
Includes bibliographical references and index.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat Reader.
Keywords: Mathematical analysis; Electronic books